Harnessing solar drying for starter cultures: A novel approach to backslopping fermentation - Marcel Houngbédji; Donan Bangbadé; D. Sylvain Dabadé; Schadrac D. Agossevi; B. Pélagie Agbobatinkpo; S. Wilfrid Padonou; Joseph Dossou; Paulin Azokpota; D. Joseph Hounhouigan (Applied Food Research)
Solar drying is a cost-effective and sustainable method for the preservation of food and food ingredient, particularly in West Africa. In this study, a locally constructed solar dryer was used to assess and model the drying kinetics of a previously developed backslop culture, while also evaluating its effectiveness in cereal fermentation. The solar drying system significantly induced a temperature gradient between outside and inside the drying chamber, enhancing inside temperature to 45.6 – 59.8 °C during the 5 h drying process, while the outside temperature ranged from 30 – 33 °C. Significant reduction of the moisture content of the backslop culture was observed, dropping from 52.3 ± 0.5 at the onset (0 h) to 9.2 ± 0.7 % at the end of the drying process. The final water activity of the dried culture was 0.17 ± 0.03, ensuring satisfactory survival of lactic acid bacteria (97.42 ± 0.15 % of viability) and yeast (81.05 ± 7.06 % of viability). The drying kinetic patterns showed consistent fit with Midili-Kucuk model with high reliable predictivity (R2 = 0.998) and least bias (Root Mean Square Error = 0.016), demonstrating the suitability of solar drying for small-scale production of starter culture. Similar to oven-dried and freeze-dried cultures for food fermentation, the solar-dried backslop starter culture resulted in desirable acidity and pH levels in subsequent fermented products. This study demonstrates the potential of solar drying as a sustainable, cost-effective alternative to energy-intensive methods like freeze- and oven-drying, while ensuring food safety through controlled fermentation.